RELEVANSI KEBIJAKAN EKONOMI NABI YUSUF PADA RESESI EKONOMI INDONESIA - Pujiono, Pujiono; Lazuardi, Afried (Sekolah Tinggi Ilmu Fikih Syeikh Nawawi Tanara Serang, 2023)
This research aims to analyze and explore the relevance of economic policies contained in the story of the Prophet Yusuf in the context of the economic recession in Indonesia. The story of the Prophet Yusuf in the Koran contains various aspects of economic policy, such as resource management, distribution policy, the role of technology, and public finance, which can be a source of inspiration for facing the economic crisis. In the Indonesian context, where economic challenges can arise from various factors such as changes in the global economy, natural disasters, or in the case of this research, the COVID-19 pandemic. Through historical and religious approaches, this research analyzes the story of the Prophet Yusuf and identifies relevant economic policy principles. Furthermore, this research compares these principles with the policies that have been implemented by the Indonesian government in dealing with the economic recession and the impact of the COVID-19 pandemic. It is hoped that the results of this research will provide useful insights and recommendations for policy makers, researchers and economic practitioners in facing complex and diverse economic challenges.